PENGARUH KECERDASAN EMOSIONAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA INDUSTRI PERCETAKAN DI DENPASAR BALI - Sari, Cintya Purnama; Indiani, Ni Luh Putu (Jurnal Manajemen, 2023)
Improving employee performance is an important aspect to achieve company goals. This study aims to determine the influence of emotional intelligence and work discipline on employee performance in printing industry in Denpasar. The population of this study are employees in printing industry. The sample used was 125 respondents. The analysis technique used is multiple linear regression analysis. The results showed that emotional intelligence and work discipline have positive and significant influence on employee performance. To improve emotional intelligence, training needs to be provided for employees to further hone their abilities to understand their own feelings, handle emotions, push themselves to a better direction, empathize, establish good relations with others, and handle disputes. Aspects that need to be considered in work discipline to improve employee performance are establishing reward and punishment system to increase compliance with attendance at work, compliance with work obligations and regulations, adherence to work standards, and level of vigilance.